TYPES OF CLASSROOM INTERACTIONS IN THE IMPLEMENTATION OF MINI DRAMA SCRIPT PROJECT (Universitas Negeri Semarang, 2015)
The study was aimed at investigating types of classroom interaction that occurred during the implementation of mini drama script project.The data were gathered through observations and audio and video recording during three cycles. The collected data were further analyzed through four steps of analyzing talks: (1) providing a general characterization in which I listened to the conversation to get a general sense of the kind of interactions, (2) identifying grossly apparent features in which I looked more closely to language features found during the conversation, (3) focusing in on structural elements in which I examined how the interactions were structured and described the most noticeable features, and (4) developing a description in which I described the findings based on the data. The results indicated the implementation of a mini drama script project allowed various types of interaction to occur during the project including the teacher speaking to the whole class, the teacher speaking to a group of members, the student speaking to teacher, the student speaking to student, and the student speaking to group members.In conclusion, the implementation of mini drama script project allows various types of classroom interaction.